ABO blood group and nasopharyngeal carcinoma risk in a population of Southeast China. Issue 4 (9th March 2013) - Sheng, Liming; Sun, Xiaojiang; Zhang, Lizhen; Su, Dan
<x xml:space="preserve">Abstract</x> Previous studies found that the ABO blood type alters the individual susceptibility of some malignancies. However, whether such an association exists between ABO blood type and nasopharyngeal carcinoma (NPC) remains unknown. A case‐control study was conducted, with 1, 538 patients who had NPC and 1, 260 cancer‐free controls. The association between ABO blood type and NPC incidence was evaluated using unconditional logistic regression analysis. Compared with subjects with blood type O, a relatively higher risk was observed among cases with blood types A or AB, with ORs (95% confidence interval) of 1.287 (1.072 − 1.545), p = 0.007 and 1.390 (1.007 − 1.919), p = 0.045, respectively, after adjusting for gender, age, smoking status and family history of cancer. The rate of distant metastasis was significantly higher among male patients with blood type A than in patients with non‐A blood types (6.8 vs. 3.5%, p = 0.027). Our results suggest that blood types A or AB is associated with an increased risk of NPC. Further studies are needed to confirm this association and to explore the mechanisms involved.